Rimpe: régimen simplificado para emprendedores y el cumplimiento de sus obligaciones formales. - Saldaña Arevalo, Ronald Andres (Universidad Técnica de Machala, 2022)
To encourage and revive entrepreneurship in Ecuador due to the global crisis due to the pandemic, the Organic Law for Economic Development and Fiscal Sustainability after the COVID-19 Pandemic is developed, which in turn adhered to the Simplified Regime for Popular Entrepreneurs and Businesses ( RIMPE), for this reason, the present research work seeks to know the formal duties that were assigned according to the taxpayers' cadastres, by virtue of the aforementioned, the main objective is to analyze the fulfillment of the formal obligations in the taxpayers. RIMPE Entrepreneur, likewise, the methodology applied is mixed, that is, it will be of a qualitative and quantitative nature; it is qualitative because a literature review will be carried out with the purpose of obtaining a broader and more accurate perspective about the new RIMPE regime, which are collected from scientific articles, books and current legal regulations, and quantitative because an exercise will be applied practical about the RIMPE Entrepreneur, according to the norms given by the Internal Revenue Service (SRI), concluding that when correctly performing the formal duties, specifically in declaring the taxes, it is essential to know the laws and regulations, to correctly execute the procedures tax, in order not to fall into tax arrears.
Para incentivar y resurgir el emprendimiento en Ecuador debido a la crisis mundial por la pandemia, se desarrolla la Ley Orgánica para el Desarrollo Económico y Sostenibilidad Fiscal tras la Pandemia COVID-19, quien a su vez adhirió el Régimen Simplificado para Emprendedores y Negocios Populares (RIMPE), por tal razón, el presente trabajo de investigación busca como finalidad conocer los deberes formales que fueron asignados de acuerdo al catastros los contribuyentes , en virtud de los antes mencionado, el objetivo principal es analizar el cumplimiento de las obligaciones formales en los contribuyentes RIMPE Emprendedor, así mismo, la metodología aplicada es mixto, es decir será de carácter cualitativo y cuantitativo; es cualitativo porque se llevará a cabo una revisión de literatura con el propósito de recabar una perspectiva más amplia y certera acerca del nuevo régimen RIMPE, la cual son recabadas de, artículos científicos, libros y normativa legal vigente, y cuantitativo porque se aplicará un ejercicio práctico acerca del RIMPE Emprendedor, de acuerdo a las normas dadas por el Servicio de Rentas Internas (SRI), concluyendo que al realizar correctamente los deberes formales, específicamente en declarar los impuesto, es fundamental conocer las leyes y normas, para ejecutar correctamente los procedimientos tributarios, con la finalidad de no caer en mora tributaria.
Keywords: RÉGIMEN SIMPLIFICADO; SUJETO PASIVO; ADMINISTRACIÓN; TRIBUTARIA